Factors Contributing to Plantar Fasciitis in Women - I Gusti Ayu Dea Rarassanti; Putu Ayu Sita Saraswati; Anak Ayu Nyoman Trisna Narta Dewi (Physical Therapy Journal of Indonesia, 2022)
Introduction: Plantar fasciitis is a degenerative syndrome that causes inflammation of the plantar fascia due to repetitive trauma and excessive stretching, which can cause a tear in the plantar fascia. This study aimed to determine the possible risk factors that affect the incidence of plantar fasciitis. Methods: This study design was the literature review. This study searched journals through Google Scholar and PubMed databases related to plantar fasciitis or the factors that influence plantar fasciitis. Results: In general, the risk factors for plantar fasciitis are classified into intrinsic and extrinsic factors. Inherent factors can be age, gender, and body mass index (BMI), while outside factors are the use of shoes and duration or standing time. Conclusions: A high BMI is a more dominant intrinsic factor in causing plantar fasciitis. Meanwhile, the use of shoes and the duration of time of standing were the more dominant external factors for the incidence of plantar fasciitis.